2018
DOI: 10.1093/nar/gky220
|View full text |Cite
|
Sign up to set email alerts
|

RNA-splicing factor SART3 regulates translesion DNA synthesis

Abstract: Translesion DNA synthesis (TLS) is one mode of DNA damage tolerance that uses specialized DNA polymerases to replicate damaged DNA. DNA polymerase η (Polη) is well known to facilitate TLS across ultraviolet (UV) irradiation and mutations in POLH are implicated in skin carcinogenesis. However, the basis for recruitment of Polη to stalled replication forks is not completely understood. In this study, we used an affinity purification approach to isolate a Polη-containing complex and have identified SART3, a pre-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Through affinity purification and mass spectrometry, SIVA1 (SIVA apoptosis-inducing factor 1), SART3 (squamous cell carcinoma antigen recognized by T Cells 3), and MAGE-A4 (melanoma associated antigen-A4) were identified as critical regulators of PCNA mono-ubiquitination in response to UV-induced DNA damage [109,110,111]. SIVA1 plays an important role in the extrinsic and intrinsic apoptotic pathways induced by the CD27 (cluster of differentiation 27) receptor, whereas SART3, a pre-mRNA splicing factor, functions in the recycling of the splicing machinery.…”
Section: Enhancers Of Pcna K164 Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through affinity purification and mass spectrometry, SIVA1 (SIVA apoptosis-inducing factor 1), SART3 (squamous cell carcinoma antigen recognized by T Cells 3), and MAGE-A4 (melanoma associated antigen-A4) were identified as critical regulators of PCNA mono-ubiquitination in response to UV-induced DNA damage [109,110,111]. SIVA1 plays an important role in the extrinsic and intrinsic apoptotic pathways induced by the CD27 (cluster of differentiation 27) receptor, whereas SART3, a pre-mRNA splicing factor, functions in the recycling of the splicing machinery.…”
Section: Enhancers Of Pcna K164 Ubiquitinationmentioning
confidence: 99%
“…SIVA1 plays an important role in the extrinsic and intrinsic apoptotic pathways induced by the CD27 (cluster of differentiation 27) receptor, whereas SART3, a pre-mRNA splicing factor, functions in the recycling of the splicing machinery. Outside their known roles in apoptosis and mRNA splicing, SIVA1 and SART3 function as adaptors for Rad18 to bind to PCNA, and promote efficient PCNA ubiquitination in response to UV radiation [109,110]. Other factors, such as MAGE-A4 do not function as a bridge between Rad18 and PCNA, but instead directly bind to Rad18 to stabilize it.…”
Section: Enhancers Of Pcna K164 Ubiquitinationmentioning
confidence: 99%
“…HAT-repeat proteins are mostly involved in protein-protein and protein-RNA interactions and act as scaffolding proteins. They participate in various RNA processing pathways, prominent examples being SART3, which is involved in splicing and translesion DNA synthesis (11) and RNA14, which is important for mRNA 3′-end maturation (12). Furthermore, a cryo-EM structure of a yeast pre-catalytic pre-B complex (13) revealed that the contact between the U1 and U2 snRNP is largely mediated by the yPrp42/yPrp39 heterodimer.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to TS, HR also belongs to the error-free branch of the DNA damage tolerance pathway (13). In contrast, TLS is referred to as the error-prone branch of DNA damage tolerance (14), and is a conserved mechanism from bacteria to mammals that recruits various specialized DNA polymerases to the stalled replication forks (1517). These specialized polymerases mostly belong to the Y family, consisting of Polη and Rev1 in yeasts, encoded by RAD30 and REV1 , respectively (18).…”
Section: Introductionmentioning
confidence: 99%